The Philippine Manufacturing Industry Roadmap: Agenda for New Industrial Policy, High Productivity Jobs, and Inclusive Growth - Rafaelita M. Aldaba (Philippine Institute for Development Studies (PIDS), 2014)
In the light of the weak performance of the Philippine manufacturing industry and the absence of structural transformation of the economy from agriculture to manufacturing in the last two decades, the paper calls for the implementation of a new industrial policy. This is crucial not only to upgrade Philippine industries, generate more and better jobs, and reduce poverty but also to take advantage of the market opportunities and face the challenges arising from the ASEAN Economic Community.Based on the sectoral roadmaps submitted by industries to the Department of Trade and Industry and Board of Investments, the paper has formulated a comprehensive industrial strategy to enable manufacturing firms to upgrade, thrive, and become catalysts and engines for sustained and inclusive growth. The long-term vision of the Manufacturing Industry Roadmap is to develop a globally competitive manufacturing industry supported by strong backward and forward linkages with both domestic and global supply chains. Through the implementation of the roadmap, manufacturing contribution to the economy would account for 30 percent of total value added and generate 15 percent of total employment.Industry policies will focus on horizontal and vertical measures and a coordination mechanism to enhance firm productivity, strengthen supply chains to enable firms to move up the technology scale, link domestic firms with multinational companies, and aggressively court more investment. Horizontal measures will cover human resource development, small and medium enterprises development, technology upgrading and innovation, investment promotion, and a competitive exchange rate policy. It will also address issues such as high power and logistics cost, smuggling, and infrastructure weaknesses. Vertical measures will address gaps in industry supply chains and expand the domestic market base as springboard for exports. A coordination mechanism will be designed to allow more interaction between government agencies and industries in identifying obstacles and determining the most appropriate interventions.The roadmap implementation will be private-sector led while the government acts as facilitator. As facilitating government, it will encourage producers to take risks, correct market and government failures, and address changes in policies and institutions. By creating the proper environment and strengthening industries, the government can promote the success of domestic firms in both the local and international markets that will lead to economic transformation. Only with the right environment can manufacturing unleash its full potentials to take advantage of the market opportunities currently facing us and become an engine for sustained and inclusive growth.
Keywords: 330; Philippines; structural transformation; manufacturing industry